P. 1
Book Geometry Problem Open Inequalities With Power Exponential Functions Conjecture4 6

Book Geometry Problem Open Inequalities With Power Exponential Functions Conjecture4 6

|Views: 15|Likes:
Published by Dung Tien Hua

More info:

Published by: Dung Tien Hua on Apr 02, 2014
Copyright:Traditional Copyright: All rights reserved

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as PDF, TXT or read online from Scribd
See more
See less

11/14/2015

pdf

text

original

SOLUTION OF ONE CONJECTURE ON INEQUALITIES WITH POWER-EXPONENTIAL FUNCTIONS

ˇ LADISLAV MATEJÍCKA
Institute of Information Engineering, Automation and Mathematics Faculty of Chemical Food Technology Slovak University of Technology in Bratislava Slovakia EMail: matejicka@tnuni.sk Received: Accepted: Communicated by: 2000 AMS Sub. Class.: Key words: Abstract: 20 July, 2009 24 August, 2009 S.S. Dragomir 26D10. Inequality, Power-exponential functions. In this paper, we prove one conjecture presented in the paper [V. Cîrtoaje, On some inequalities with power-exponential functions, J. Inequal. Pure Appl. Math. 10 (2009) no. 1, Art. 21. http://jipam.vu.edu.au/article.php? sid=1077]. The author is deeply grateful to Professor Vasile Cîrtoaje for his valuable remarks, suggestions and for his improving some inequalities in the paper.

Solution Of One Conjecture Ladislav Matejíˇ cka vol. 10, iss. 3, art. 72, 2009

Title Page Contents

Page 1 of 12 Go Back Full Screen Close

Acknowledgements:

art. iss. 10.6 3 4 Solution Of One Conjecture Ladislav Matejíˇ cka vol.Contents 1 2 Introduction Proof of Conjecture 4. 72. 3. 2009 Title Page Contents Page 2 of 12 Go Back Full Screen Close .

1) arb + bra ≤ 2 Solution Of One Conjecture Ladislav Matejíˇ cka vol. art. V. In this paper.6.6.1. iss. The inequality (1. 72. Cîrtoaje posted 5 conjectures on inequalities with power-exponential functions. 10. if and only if r ≤ 3. 3. Conjecture 4. Title Page Contents Page 3 of 12 Go Back Full Screen Close . Introduction In the paper [1]. Let r be a positive real number. 2009 holds for all nonnegative real numbers a and b with a + b = 2. we prove Conjecture 4.

then 0 < t < 1. Put t = x . Proof of Conjecture 4. 10. it suffices to show that α (t) < 0 for t0 < t < 1. Then we have (2.7401 such that β (t0 ) = 0 and we have that β (t) ≤ 0 for 6 0 ≤ t ≤ t0 . Put a = 2 − x .1) will be x 1 fulfilled for all x > 1. art.2. The inequality (2.1) In fact. and from that there is only one real t0 = 0.1) becomes Title Page Contents t > t3 (t3 − 6t2 + 12t − 6) = t3 β (t). β (0) = −6. iss. Thus. 1 2− x 3 arb + bra > 2.6 1 1 First. 2009 1 1 6 and if we show that x > −6 + 12 −x 2 + x3 then the inequality (2. we prove the necessary condition. where α (t) = − 6 ln t + t2 6 −3 t 1 3t2 − 12t + 12 − 3 . r = 3x for x > 1.b= x . 3. it suffices to show that t t > t3 β (t) for t0 < t < 1. From β (t) = 3(t − 2)2 . t 6 t Page 4 of 12 Go Back Full Screen Close From α(1) = 0. Rewriting the previous inequality we get α(t) = 6 − 3 ln t − ln(t3 − 6t2 + 12t − 6) > 0. where β (t) = t3 − 6t2 + 12t − 6. Solution Of One Conjecture + 1 x 6 x− 3 1 3x(2− x ) 12 6 1 =8− + 2− 3+ x x x 1 x 6 x− 3 Ladislav Matejíˇ cka vol. 72. t t − 6t2 + 12t − 6 .

t3 − 6t2 + 12t − 6 From γ (1) = 0. 10.74) = 5. 3. 72.2) q (t) = t6 − 10t5 + 36t4 − 42t3 − 30t2 + 90t − 36 > 0. we have q (t) = 2(15t − 100t + 216t − 126t − 30) < 2(40t4 − 100t3 + 216t2 − 126t − 30) = 4(t − 1)(20t3 − 30t2 + 78t + 15) < 4(t − 1)(−30t2 + 78t) < 0.893. art. Page 5 of 12 Go Back Full Screen Close 7 6 5 4 3 2 Solution Of One Conjecture Ladislav Matejíˇ cka vol. 2009 Title Page Contents γ (t) < 0 is equivalent to Since q (0. iss. From p(t) = 2(t − 1)(t6 − 10t5 + 36t4 − 42t3 − 30t2 + 90t − 36). (t3 − 6t2 + 12t − 6)2 t p(t) = 2t − 22t + 92t − 156t + 24t + 240t − 252t + 72 < 0. for t0 < t < 1.2) will be proved. it suffices to show that γ (t) < 0 for t0 < t < 1. Indeed. it suffices to show that (2.α (t) < 0 is equivalent to t2 (t − 2)2 > 0. where γ (t) = 2 ln t − 2 + t + γ (t) = (4t3 − 12t2 + 8t)(t3 − 6t2 + 12t − 6) − (t4 − 4t3 + 4t2 )(3t2 − 12t + 12) (t3 − 6t2 + 12t − 6)2 2 + +1 t t6 − 12t5 + 56t4 − 120t3 + 120t2 − 48t 2 = + + 1. 4 3 2 . q (1) = 9 it suffices to show that q (t) < 0 and (2.

we only need to show that (2. Therefore. 1−x 1+x Title Page Contents The inequality ϕ (x) < 0 is equivalent to (2. 10. 72. iss.3) (1 − x)r(1+x) + (1 + x)r(1−x) ≤ 2 for 0 < x < 1. 0 < r ≤ 3. ϕ (x) = (1−x)r(1+x) r ln(1 − x) − r 1+x 1−x +(1+x)r(1−x) r − r ln(1 + x) . δ (0) = 1 and δ (1) = − ln 2. art.3) is valid (ϕ(0) = 2).4547. where 0 < x < 1. Solution Of One Conjecture Ladislav Matejíˇ cka vol. Then from h(0) = 0 we obtain . 0 < r ≤ 3. 3. We show that ϕ (x) < 0 for 0 < x < 1. it suffices to show that h(x) ≥ 0 for 0 ≤ x ≤ x0 .This completes the proof of the necessary condition. we have δ (x) > 0 for 0 ≤ x < x0 ∼ = 0.4) is evident. We prove the sufficient condition. 1+x We show that h (x) ≥ 0 for 0 < x < x0 . 1−x Page 6 of 12 Go Back Full Screen Close −x 2 1 If δ (x) = 1 − ln(1+ x) ≤ 0.4) 1+x 1−x r 1−x − ln(1 + x) 1+x ≤ (1 − x2 )rx 1+x − ln(1 − x) . Put a = 1 − x and b = 1 + x. 0 < r ≤ 3 which gives that (2. 2009 Denote ϕ(x) = (1 − x)r(1+x) + (1 + x)r(1−x) . Since the desired inequality is true for x = 0 and for x = 1. where h(x) = rx ln(1 − x2 ) − r ln 1+x 1−x + ln 1+x − ln(1 − x) 1−x 1−x − ln − ln(1 + x) . Since δ (x) = − (1+ − 1+ <0 1+x x) 2 x for 0 ≤ x < 1. then (2.

It is easy to show that the following Taylor’s formulas are valid for 0 < x < 1: ∞ 2 4 4 3 2 4 3 2 Page 7 of 12 Go Back Full Screen Close A= n=0 (−1)n n+1 x .5) will be fulfilled for 0 < r ≤ 3. 0 < x < x0 is equivalent to (2.4) is valid. it suffices to prove that (2. 3. (1 + x)(1 − x − (1 + x) ln(1 + x)) Solution Of One Conjecture Ladislav Matejíˇ cka vol. h (x) = r ln(1 − x2 ) − 2r 1 + x2 3−x + 2 1−x (1 − x)(1 + x − (1 − x) ln(1 − x)) 3+x + . The inequality (2.6) for 0 < x < x0 is equivalent to (2.6) 3(2x2 + 2 − (1 − x2 )(A + B )) ≤ 3 − 2x − x2 3 + 2x − x2 + 1 − x − (1 + x)A 1 + x − (1 − x)B and then the inequality (2. 1 − x − (1 + x)A 1 + x − (1 − x)B Title Page Contents Since 2x2 + 2 − (1 − x2 )(A + B ) > 0 for 0 < x < 1.5) r(2x2 + 2 − (1 − x2 )(A + B )) ≤ 3 + 2x − x2 3 − 2x − x2 + . 72.7) 6x − 6x − (9x +13x +5x +7x +6)A − (9x − 13x +5x − 7x +6)B − (3x4 + 6x3 − 6x − 3)A2 − (3x4 − 6x3 + 6x − 3)B 2 − (12x4 − 12)AB − (3x4 − 6x2 + 3)AB (A + B ) ≤ 0. 10. n+1 ∞ B=− n=0 1 xn+1 . n+1 . 2009 Put A = ln(1 + x) and B = ln(1 − x). art. The inequality h (x) ≥ 0. iss.h(x) ≥ 0 for 0 < x ≤ x0 and it implies that the inequality (2.

6 90 1 − x2 From this and from the previous Taylor’s formulas we have (2.∞ A2 = n=1 2(−1)n+1 n+1 AB = − n i=1 ∞ 1 i ∞ xn+1 . art.5. B2 = n=1 2 n+1 x2n+2 . 11 137 6 2x8 = 2x + x4 + x + . iss.5. 2 i=1 1 i xn+1 n 11 137 6 4 = 2x + x4 + x + 6 90 n+1 n=7.. 3..9.. ...3.. 10... 2009 and 4 n+1 we have A2 + B 2 = n i=1 1 i ≤ 4 n+1 n 1+ n−1 2 = 2.9. n=0 1 n+1 2n+1 i=1 (−1) i i+1 Since 4 A +B = n+1 n=1. n i=1 1 i xn+1 .... 72. Title Page Contents 4 n+1 n=1..8) 1 1 1 A + B > −x2 − x4 − x6 − 2 3 4 x8 1 − x2 . 2 2 n i=1 1 i xn+1 Solution Of One Conjecture Ladislav Matejíˇ cka vol. < 2x2 + 2 i=1 1 i xn+1 Page 8 of 12 Go Back Full Screen Close 11 4 137 6 x + x +2 xn+1 6 90 n=7.3.

iss.(2. art.11) 5 A2 − B 2 < −2x3 − x5 . to prove (2.12) and the obvious inequality A + B < 0. 3 5 7 2x8 11 4 137 6 x + x + . (2. having in view (2.11). 3. 10. the previous inequality will be proved if we Page 9 of 12 Go Back Full Screen Close . 6 90 1 − x2 (2. 72. 2009 Title Page (2.9) 2 2 2 A − B > 2x + x3 + x5 + x7 . 3 AB < −x2 − 5 4 x 12 vol.12) for 0 < x < 1.7) it suffices to show that 6x2 − 6x4 − (6 + 5x2 + 9x4 )(A + B ) + (7x + 13x3 )(B − A) + (3 − 3x4 )(A2 + B 2 ) 5 + (6x − 6x3 )(A2 − B 2 ) − (12 − 12x4 ) x2 + x4 12 5 + x2 + x4 (3 − 6x2 + 3x4 )(A + B ) ≤ 0. 12 By using the inequalities (2. Contents Now.10).10) A2 + B 2 < 2x2 + Solution Of One Conjecture Ladislav Matejíˇ cka (2.

Since 0 < x < ε(x) = −8x2 − we have 1 1 − x2 <4 . If we show 3 259 4 357 6 1841 8 337 10 19 12 x + x + x + x − x 6 20 120 420 24 5 14 2 55 1 5 − x + 2x8 + x10 + x12 − x14 − x16 < 0. Solution Of One Conjecture Ladislav Matejíˇ cka vol. iss.14) − 8x2 − 259 4 357 6 1841 8 337 10 19 12 5 x + x + x + x − x − x14 6 20 120 420 24 12 x8 3 1 2 55 4 1 6 5 8 + + x + x − x − x 1 − x2 2 2 16 8 16 1 2 Page 10 of 12 Go Back < 0.9).13) it suffices to show (2. Full Screen Close It follows from (2. 12 3 12 6 12 .13) − 35 4 377 6 19 8 137 10 x + x + x − x + 6(x8 + x10 ) 2 30 2 30 55 1 5 − (A + B ) 6 + 2x2 + x4 − x6 − x8 4 2 4 + (7x + 13x3 )(B − A) ≤ 0. 10.8) and (2. art. 2009 Title Page Contents To prove (2.show that 6x2 − 6x4 − (6 + 5x2 + 9x4 )(A + B ) + (7x + 13x3 )(B − A) 11 137 6 2x8 5 5 3 3 + (3 − 3x4 ) 2x2 + x4 + x + − (6 x − 6 x ) 2 x + x 6 90 1 − x2 3 5 5 − (12 − 12x4 ) x2 + x4 + x2 + x4 (3 − 6x2 + 3x4 )(B + A) ≤ 0. 12 12 which can be rewritten as (2. 3. 72.

iss. 7 12 12 Title Page Contents Page 11 of 12 Go Back Full Screen Close . Solution Of One Conjecture Ladislav Matejíˇ cka vol. x8 < x4 . art. x10 < x4 and x12 < x4 . From x6 < x4 . 72.then the inequality (2. 3. we obtain that ε(x) < −8x2 − This completes the proof. 10. 2009 19 4 7 5 x − x14 − x16 < 0.14) will be proved.

vu.edu. art. 3. On some inequalities with power-exponential functions. Art. 21. 2009 Title Page Contents Page 12 of 12 Go Back Full Screen Close . Inequal. CÎRTOAJE. 72. Pure Appl. iss..au/article. [ONLINE: http://jipam. Math.References [1] V. 10. J.php?sid=1077] Solution Of One Conjecture Ladislav Matejíˇ cka vol. 10(1) (2009).

You're Reading a Free Preview

Download
scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->